2020
DOI: 10.3390/ijerph17124185
|View full text |Cite
|
Sign up to set email alerts
|

Let the Children Listen: A First Approximation to the Sound Environment Assessment of Children through a Soundwalk Approach

Abstract: The urban sound environment is one of the layers that characterizes a city, and several methodologies are used for its assessment, including the soundwalk approach. However, this approach has been tested mainly with adults. In the work presented here, the aim is to investigate a soundwalk methodology for children, analyzing the sound environment of five different sites of Gothenburg, Sweden, from children’s view-point, giving them the opportunity to take action as an active part of society. Both individual ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The questionnaire is based on previous ones used to study the sound environment in the city of Gothenburg. 37 Moreover, a set of additional questions was added based on the research performed by Kang et al 3840 The questionnaires were available in both Swedish and English. The first page explained the instructions as well as the confidentiality treatment of the data in this voluntary study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire is based on previous ones used to study the sound environment in the city of Gothenburg. 37 Moreover, a set of additional questions was added based on the research performed by Kang et al 3840 The questionnaires were available in both Swedish and English. The first page explained the instructions as well as the confidentiality treatment of the data in this voluntary study.…”
Section: Methodsmentioning
confidence: 99%
“…The second set of questions dealt with the suitable activities for the specific location, responding to the previous study carried out in the city of Gothenburg, 37 together with the list of sociotopes developed by the city 29 and the research done by Lavia et al 21 The list and their abbreviations, used from now on in this study, are shown in Table 3 with a scale of 1–5 (‘not applicable, slightly, moderately, very and perfectly’).…”
Section: Methodsmentioning
confidence: 99%
“…However, existing studies involving acoustic environments for children have mainly focused on the detrimental effects of annoying noise, especially traffic noise and noise generated by the children themselves, which are the most prevalent background sounds in their daily environments ( Lercher et al, 2013 ; Estévez-Mauriz et al, 2020 ). To date, only a few have indicated the possible benefits of some noise on children’s performance ( Söderlund et al, 2007 ), and even fewer have looked at the positive role of overall soundscapes in children’s experiences.…”
Section: Introductionmentioning
confidence: 99%